Surveillance system evaluation of non-communicable diseases through integrated community-based intervention called ‘Posbindu PTM’ in Wonosobo district, Central Java province, Indonesia - Rieski Prihastuti; Trisno Agung Wibowo; Misinem Misinem (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Purpose: Non-communicable diseases are leading cause of the global death, especially from cardiovascular disease, cancers, chronic obstructive pulmonary disease, and diabetes. Prevention and primary detection of non-communicable disease in Indonesia were done through integrated community-based intervention called ‘Posbindu PTM’. Implementation of ‘Posbindu PTM’ needed to be evaluated to determine each component in the non-communicable disease surveillance systems. Methods: This study was descriptive. Respondent were programmer in district health office and programmer in 24 primary health care in Wonosobo. Surveillance system evaluation that used was programs evaluation based on WHO (structure, main function, support function and quality of surveillance system). Results: The weakness of ‘Posbindu PTM’ in Wonosobo were lack of knowledge in the regulation, networking, collaborating, risk factor detecting and reporting; not availability of technical guidebook; low training participant; low monitoring and evaluation activity; also complex reporting system. There was 84% ‘Posbindu PTM’ that had not reported on time and 87,50 % programmer had not done the analysis, interpretation, and dissemination. This was related to the completeness of the report caused too many data that needed to be collected and affect the timeliness of the report. Conclusion: Strengthening ‘Posbindu PTM’ should be done in the reporting system aspect, especially in the timeliness and analysis of the report. Monthly reminder and refreshing in reporting system were done to improve the reporting system aspect.